Live Imaging of Shoot Meristems on an Inverted Confocal Microscope Using an Objective Lens Inverter Attachment - Nimchuk, Zachary L.; Perdue, Tony D. (Frontiers in Plant Science, 2017)
Live imaging of above ground meristems can lead to new insights in plant development not possible from static imaging of fixed tissue. The use of an upright confocal microscope offers several technical and biological advantages for live imaging floral or shoot meristems. However many departments and core facilities possess only inverted confocal microscopes and lack the funding for an additional upright confocal microscope. Here we show that imaging of living apical meristems can be performed on existing inverted confocal microscopes with the use of an affordable and detachable InverterScope accessory.